Recombinant probiotic Lactococcus lactis delivering P62 mitigates moderate colitis in mice - Laguna, Juliana Guimarães; Freitas, Andria dos Santos; Barroso, Fernanda Alvarenga Lima; De Jesus, Luís Cláudio Lima; De Vasconcelos, Octávio Augusto Greco Gomes; Quaresma, Ludmila Silva; Américo, Monique Ferrary; Campos, Gabriela Munis; Glória, Rafael de Assis; Dutra, Joyce da Cruz Ferraz; Da Silva, Tales Fernando; Vital, Kátia Duarte; et al. (Frontiers in Microbiology, 2024)
p62 is a human multifunctional adaptor protein involved in key cellular processes such as tissue homeostasis, inflammation, and cancer. It acts as a negative regulator of inflammasome complexes. It may thus be considered a good candidate for therapeutic use in inflammatory bowel diseases (IBD), such as colitis. Probiotics, including recombinant probiotic strains producing or delivering therapeutic biomolecules to the host mucosal surfaces, could help prevent and mitigate chronic intestinal inflammation. The objective of the present study was to combine the intrinsic immunomodulatory properties of the probiotic Lactococcus lactis NCDO2118 with its ability to deliver health-promoting molecules to enhance its protective and preventive effects in the context of ulcerative colitis (UC). This study was realized in vivo in which mice were supplemented with the recombinant strain. The intestinal barrier function was analyzed by monitoring permeability, secretory IgA total levels, mucin expression, and tight junction genes. Its integrity was evaluated by histological analyses. Regarding inflammation, colonic cytokine levels, myeloperoxidase (MPO), and expression of key genes were monitored.The intestinal microbiota composition was investigated using 16S rRNA Gene Sequencing. As a result, no protective effect of L. lactis NCDO2118 pExu:p62 was observed regarding mice clinical parameters compared to the L. lactis NCDO2118 pExu: empty. However, the recombinant strain, expressing p62, increased the goblet cell counts, upregulated Muc2 gene expression in the colon, and downregulated pro-inflammatory cytokines Tnf and Ifng when compared to L. lactis NCDO2118 pExu: empty and inflamed groups. This recombinant strain also decreased colonic MPO activity. No difference in the intestinal microbiota was observed between all treatments. Altogether, our results show that recombinant L. lactis NCDO2118 delivering p62 protein protected the intestinal mucosa and mitigated inflammatory damages caused by dextran sodium sulfate (DSS). We thus suggest that p62 may constitute part of a therapeutic approach targeting inflammation.